Basic Provisions of the Clinton Plan, National Senior Group Applauds Clinton Health Proposals, Clinton Goes Face to Face with Public on Health Care, Preliminary Tax and Preemption Target States - SUSAN STUNTZ (Tufts Archival Research Center, 2007)
Collection of documents pertaining to the suggested cigarette tax as a means of funding the Clinton Health Plan. Includes a Citizen Action summary of the basic components of the health care plan, a press release from the National Council of Senior Citizens applauding the Clinton plan, and numerous cover memos from Susan Stuntz. Contains article on a Clinton meeting and 1994 cigarette tax projections covering preliminary tax and preemption target states for 1994..